Left Ventricle Blood Attenuation in Non-Contrast Chest CT Scan as a Clue for Prediction of Anemia - Hamid Dahmardeh; Aynaz Gerami; Mahmoud Khansari; Leyla Abdolkarimi; Seyede Sara Pakdaman Kolour; Majid Ghodsi; Hoseinali Danesh; Mohamad Ghazanfari Hashemi (Frontiers in Biomedical Technologies)
Purpose: One of the indirect methods that has been proposed as a way of the detection of anemia is blood attenuation in non-contrast Computed Tomography (CT) scans. Some indices of non-contrast CT scans have been studied as a clue. Most known of such indices include aortic blood density and the difference between blood density and aortic wall density. In the current study, we aimed to evaluate the left ventricle blood attenuation and its relation to patients’ hemoglobin levels.